Pacemaker cell characteristics of differentiated and HCN4-transduced human mesenchymal stem cells - Darche, Fabrice Fernand; Rivinius, Rasmus; Köllensperger, Eva; Leimer, Uwe; Germann, Günter; Seckinger, Anja; Hose, Dirk; Schröter, Julian; Bruehl, Claus; Draguhn, Andreas; Gabriel, Richard; Schmidt, Manfred; et al. (Life sciences, 2019)
Aims - Cell-based biological pacemakers aim to overcome limitations and side effects of electronic pacemaker devices. We here developed and tested different approaches to achieve nodal-type differentiation using human adipose- and bone marrow-derived mesenchymal stem cells (haMSC, hbMSC). - Main methods - haMSC and hbMSC were differentiated using customized protocols. Quantitative RT-PCR was applied for transcriptional pacemaker-gene profiling. Protein membrane expression was analyzed by immunocytochemistry. Pacemaker current (If) was studied in haMSC with and without lentiviral HCN4-transduction using patch clamp recordings. Functional characteristics were evaluated by co-culturing with neonatal rat ventricular myocytes (NRVM). - Key findings - Culture media-based differentiation for two weeks generated cells with abundant transcription of ion channel genes (Cav1.2, NCX1), transcription factors (TBX3, TBX18, SHOX2) and connexins (Cx31.9 and Cx45) characteristic for cardiac pacemaker tissue, but lack adequate HCN transcription. haMSC-derived cells revealed transcript levels, which were closer related to sinoatrial nodal cells than hbMSC-derived cells. To substitute for the lack of If, we performed lentiviral HCN4-transduction of haMSC resulting in stable If. Co-culturing with NRVM demonstrated that differentiated haMSC expressing HCN4 showed earlier onset of spontaneous contractions and higher beating regularity, synchrony and rate compared to co-cultures with non-HCN4-transduced haMSC or HCN4-transduced, non-differentiated haMSC. Confocal imaging indicated increased membrane expression of cardiac gap junctional proteins in differentiated haMSC. - Significance - By differentiation haMSC, rather than hbMSC attain properties favorable for cardiac pacemaking. In combination with lentiviral HCN4-transduction, a cellular phenotype was generated that sustainably controls and stabilizes rate in co-culture with NRVM.
Gesehen am 08.12.2020